Combination of early rhythm control and healthy lifestyle on the risk of stroke in elderly patients with new-onset atrial fibrillation: a nationwide population-based cohort study - Lim, Woo-Hyun; Lee, So-Ryoung; Choi, Eue-Keun; Lee, Seung-Woo; Han, Kyung-Do; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2024)
Background The impact of early rhythm control (ERC) combined with healthy lifestyle (HLS) on the risk of ischemic stroke in elderly patients with atrial fibrillation (AF) remains unaddressed. Objective To evaluate the impact of combined ERC and HLS on the risk of stroke in elderly patients with new-onset AF. Methods Using the Korean National Health Insurance Service database, we included patients aged ≥75 years with new-onset AF from January 2009 to December 2016 (n = 41,315). Patients who received rhythm control therapy within 2 years of AF diagnosis were defined as the ERC group. Non-smoking, non-to-mild alcohol consumption (<105 g/week), and regular exercise were defined as HLS. Subjects were categorized into four groups: group 1 (without ERC and HLS, n = 25,093), 2 (HLS alone, n = 8,351), 3 (ERC alone, n = 5,565), and 4 (both ERC and HLS, n = 2,306). We assessed the incidence of ischemic stroke as the primary outcome, along with admissions for heart failure, all-cause death, and the composite of ischemic stroke, admission for heart failure, and all-cause death. Results Median follow-up duration of the study cohort was 3.4 years. After adjusting for multiple variables, groups 2 and 3 were associated with a lower stroke risk (adjusted hazard ratio [aHR]: 95% confidence interval [CI]: 0.867, 0.794–0.948 and 0.713, 0.637–0.798, respectively) than that of group 1. Compared to Group 1, group 4 showed the lowest stroke risk (aHR: 0.694, 95% CI: 0.586–0.822) among all groups, followed by group 3 (0.713, 0.637–0.798) and group 2 (0.857, 0.794–0.948), respectively. Group 4 was associated with the lowest risk of all-cause death (aHR: 0.680, 95% CI: 0.613–0.754) and the composite outcome (aHR: 0.708, 95% CI: 0.649–0.772). Conclusion ERC and HLS were associated with a lower risk of ischemic stroke in elderly patients with new-onset AF. Concurrently implementing ERC and maintaining HLS was associated with the lowest risk of death and the composite outcome, with a modest synergistic effect on stroke prevention.